MOTIVATION TEENAGERS BECOME MEMBER OF PUNK COMMUNITY ( CASE STUDY ON A STREET PUNK COMMUNITY AT TAMBUSAI STREET PEKANBARU CITY ) - Denita, Wirma (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Adolescence is the transition to where the state of emotion not yet stable so very easily accept changes. Changes that occurred was the emergence of the punk  community and it’s is no stranger in people ear’s. Punk as a esistance to capitalism that happened anciently until now. That they show with the fancy appearance and and different activities. Mowhak hair , ears and the nose pierced ( percing ) , boots , a chain , black clothes , jeans and tattoo inherent in their body are the  fancy apperance of them with  activities like of singing for money and gathered fellow punk be a negative connotation in the eyes of the general public. Then what motivation teenager so choose a member of the punk community? This research is useful to answer that problems on,  with  6 members of punk community that found in different places as the subject or informants in this research. Data collection method through observation and in-depth interviews with members of the punk. Community. The results of research that served in a qualitative descriptive showed motivation instrinsik teenagers become a member of punk community are  appearance and comfort while Extrinsic motivation are  family and influence their peers. The fact community of punk its can  fulfill their  need based  motivation, Who served using McCelland theory , but the results of research shows the needs for power not found in the punk community. Then the views themselves against punk very positive including their view on the community that they consider punk also part therein. Key Words : Motivation,  Teenagers,  Punk Community And Self – Concept